(untitled) (Bangladesh Journal of Agricultural Research, 2022)
A field trial was conducted at the multi-location testing (MLT) site, Moulvibazar, Bangladesh during two consecutive years of 2017-2018 and 2018- 2019 located in Agro Ecological Zone (AEZ)-20; under Eastern Surma Kushiyara Floodplain to introduce maize in zero tillage as relay and after harvest of T. aman rice. Four sowing dates of maize seed viz. T1: 10 November as relay with T. aman rice, T2: 20 November as relay with T. aman rice, T3: 30 November in T. aman harvested fallow land and T4: 10 December in T. aman harvested fallow land were used as treatment variables. The trial was laid out in a randomized complete block design with three replications. Maize var. BARI Hybrid Maize-9 and short duration T. aman rice var. BRRI dhan56 /BRRI dhan57 were used. Sowing time is critical for maximizing yield for both grain and biomass yield of maize. Yield and yield attributes of maize varied significantly due to different sowing dates. The result showed that grain yields of maize 8.48, 11.20, 8.22 and 7.98 t ha-1 were achieved with seed sown on 10 November as relay with T. aman rice, 20 November as relay with T. aman rice, 30 November in T. aman harvested fallow land and 10 December in T. aman harvested fallow land, respectively. The highest grain yield (11.20 t ha-1) was obtained when sowing on 20 November as relay with T. aman rice, which showed an increase of grain yield of 40, 36 and 32 % than 10 December in T. aman harvested fallow land, 30 November in T. aman harvested fallow land and 10 November as relay with T. aman rice, respectively. The highest gross return (Tk. 2,30,095 ha-1), net return (Tk. 1,33,845 ha-1) and benefit cost ratio (2.39) were noted in the same treatment indicated the profitability of maize in zero tillage as relay with T. aman rice in AEZ 20. Bangladesh J. Agril. Res. 45(3): 239-246, September 2020